2012
DOI: 10.1007/s00418-012-0988-2
|View full text |Cite
|
Sign up to set email alerts
|

Cofilin overexpression affects actin cytoskeleton organization and migration of human colon adenocarcinoma cells

Abstract: The dynamic reorganization of actin cytoskeleton is regulated by a large number of actin-binding proteins. Among them, the interaction of ADF/cofilin with monomeric and filamentous actin is very important, since it severs actin filaments. It also positively influences actin treadmilling. The activity of ADF/cofilin is reversibly regulated by phosphorylation and dephosphorylation at Ser-3, with the phosphorylated form (P-cofilin) being inactive. Here, we studied the effects of overexpression of cofilin and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 59 publications
(82 reference statements)
0
33
0
2
Order By: Relevance
“…More importantly of direct clinically relevance are the data demonstrating a significant increase in cofilin expression in human prostate cancer metastasis (to lymph nodes), compared with primary tumors (same patient cohort). Changes in cofilin expression have been reported in other human malignancies, including colon and ovarian cancer (45-48). Loss of the epithelial marker E-cadherin is associated with a more invasive phenotype in prostate cancer cells and high-grade and metastatic prostate cancer, as originally established (49).…”
Section: Discussionmentioning
confidence: 94%
“…More importantly of direct clinically relevance are the data demonstrating a significant increase in cofilin expression in human prostate cancer metastasis (to lymph nodes), compared with primary tumors (same patient cohort). Changes in cofilin expression have been reported in other human malignancies, including colon and ovarian cancer (45-48). Loss of the epithelial marker E-cadherin is associated with a more invasive phenotype in prostate cancer cells and high-grade and metastatic prostate cancer, as originally established (49).…”
Section: Discussionmentioning
confidence: 94%
“…et al have reported that over-expression of cofilin-1 mediated motility of glioblastoma cells is concentration dependent [8]. However, another report shows that over-expression of serine-3 phosphorylated mutant cofilin-1 (S3D) results in an almost complete inhibition of cell motility in human colon adenocarcinoma cells [51]. Although wild-type cofilin-1 was induced to express in our cell model, it can be normally phosphorylated on serine-3 [6].…”
Section: Discussionmentioning
confidence: 85%
“…29 To our knowledge, lower concentrations are not used. Our previous experience 21,30 indicates that the optimal EGF concentration to stimulate cell migration/invasion is 31 ng/mL (5 nM). We decided to use HGF at the same concentration as EGF.…”
Section: Resultsmentioning
confidence: 99%